Evaluating Activities in English Textbooks: Genre-Based Approach in Indonesian Contexts - Tri Wiratno; Agus Dwi Priyanto; Djatmika Djatmika; Riyadi Santosa (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2022)
The objective of this research is to evaluate whether the activities of two nationally-recognized English textbooks satisfy the GBA (Genre-Based Approach) and the three aspects of national curriculum, involving knowledge, skills, and attitudes. The data of the research rely on the learning-teaching activities in the two English textbooks used in Class VII, VIII, and IX of Junior High Schools in Indonesia. The sources of data are taken purposively to find five different genres involving description, recount, procedure, narrative, and report. The bases of the evaluation of the book activities are derived from GBA teaching and learning processes which include the completeness, appropriate sequence, and the ampleness of the activities in satisfying the integrations of the three aspects of the national curriculum, GBA activities and language levels activities as realized in general activities. The findings indicate that the activities in the two books can be classified into two patterns. Pattern 1, in general, satisfies the completeness of the GBA and three language levels activities. However, they lack of the appropriate sequences and ampleness of the GBA and language levels and therefore, they miss the integration of the three aspects of curriculum. Pattern 2 do not satisfy all of the three bases of evaluation including completeness, appropriate sequence and ampleness of GBA and language levels activities. Therefore, the activities of the two textbooks need to be redesigned according to the integration of the three aspects of the national curriculum and the completeness, appropriate sequence, and ampleness of the GBA and language levels activities.